Evaluation criteria for information retrieval systems. - Julian Warner (Information Research: An International Electronic Journal)
The contrast between the value placed on discriminatory power in discussions of indexing and classification and on the transformation of a query into a set of relevant records dominant in information retrieval research has not been fully explored. Subsidiary concepts and measures (relevance and precision and recall) have been increasingly subjected to critiques. An enhanced capacity for informed choice is advocated as an alternative principle for system evaluation and design. This broadly corresponds to: the exploratory capability discussed in recent information retrieval research; the value of discriminatory power in classification and indexing; Giambattista Vicos critique of the unproductivity of Aristotelian methods of categorisation as routes to new knowledge; and, most significantly, to ordinary discourse conceptions of the value of information retrieval systems.